Role of EXO1 nuclease activity in genome maintenance, the immune response and tumor suppression in Exo1D173A mice. Issue 14 (18th July 2022) - Wang, Shanzhi; Lee, Kyeryoung; Gray, Stephen; Zhang, Yongwei; Tang, Catherine; Morrish, Rikke B; Tosti, Elena; van Oers, Johanna; Amin, Mohammad Ruhul; Cohen, Paula E; MacCarthy, Thomas; Roa, Sergio; et al.
Abstract: DNA damage response pathways rely extensively on nuclease activity to process DNA intermediates. Exonuclease 1 (EXO1) is a pleiotropic evolutionary conserved DNA exonuclease involved in various DNA repair pathways, replication, antibody diversification, and meiosis. But, whether EXO1 facilitates these DNA metabolic processes through its enzymatic or scaffolding functions remains unclear. Here, we dissect the contribution of EXO1 enzymatic versus scaffolding activity by comparing Exo1 DA/DA mice expressing a proven nuclease-dead mutant form of EXO1 to entirely EXO1-deficient Exo1 − / − and EXO1 wild type Exo1 +/+ mice. We show that Exo1 DA/DA and Exo1 – /–  mice are compromised in canonical DNA repair processing, suggesting that the EXO1 enzymatic role is important for error-free DNA mismatch and double-strand break repair pathways. However, in non-canonical repair pathways, EXO1 appears to have a more nuanced function. Next-generation sequencing of heavy chain V region in B cells showed the mutation spectra of Exo1 DA/DA mice to be intermediate between Exo1 +/ + and Exo1 – /– mice, suggesting that both catalytic and scaffolding roles of EXO1 are important for somatic hypermutation. Similarly, while overall class switch recombination in Exo1 DA/DA and Exo1 – /–  mice was comparably defective, switch junction analysis suggests that EXO1 might fulfill an additional scaffolding function downstream of class switching. In contrast to Exo1 − / − mice that are infertile, meiosis progressed normally in Exo1 DA/DA and Exo1 +/+ cohorts, indicating that a structural but not the nuclease function of EXO1 is critical for meiosis. However, both Exo1 DA/DA and Exo1 – / –  mice displayed similar mortality and cancer predisposition profiles. Taken together, these data demonstrate that EXO1 has both scaffolding and enzymatic functions in distinct DNA repair processes and suggest a more composite and intricate role for EXO1 in DNA metabolic processes and disease.